1.A 2.A 3.D 4. 2 8/15 I’m not sure about the the question 3
Answer:
€1333.33
Step-by-step explanation:
Al Tom ratio to Joe=5:4
Joe gets 1.5 times the amount Al gets
€3000 in the ratio 5:4
Al share
5/9×3000
=€1666.67
Joe share
4/9×3000
=€1333.33
Answer:
height is 15
Y = L = Length
therefore 15y = (-x^2) +(300/20)
Step-by-step explanation:
15 = -x^2 +(300/20)
is the same as;
15 = (300/20) - (x^2)
we just add y to 15 and that can represent a division for x
y = L
Where area cm^2 can be shown as 300 as 15 x 20 = 300
when we divide by length we get the height as asked in the question.
An equation which shows a valid step that can be used to solve the given mathematical equation is ![(\sqrt[3]{2x - 6})^3 = (-\sqrt[3]{2x + 6})^3](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B2x%20-%206%7D%29%5E3%20%3D%20%28-%5Csqrt%5B3%5D%7B2x%20%2B%206%7D%29%5E3)
<h3>What is an equation?</h3>
An equation simply refers to a mathematical expression that can be used to show the relationship existing between two (2) or more numerical quantities.
In this exercise, you're required to show a valid step which can be used to solve the given mathematical equation. Since both equations are having a cube root, the first step is to take the cube of both sides.
Take the cube of both sides, we have:
![\sqrt[3]{2x - 6} + \sqrt[3]{2x + 6} = 0\\\\(\sqrt[3]{2x - 6})^3 + (\sqrt[3]{2x + 6})^3 = 0^3\\\\(\sqrt[3]{2x - 6})^3 = (-\sqrt[3]{2x + 6})^3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x%20-%206%7D%20%2B%20%5Csqrt%5B3%5D%7B2x%20%2B%206%7D%20%3D%200%5C%5C%5C%5C%28%5Csqrt%5B3%5D%7B2x%20-%206%7D%29%5E3%20%2B%20%28%5Csqrt%5B3%5D%7B2x%20%2B%206%7D%29%5E3%20%3D%200%5E3%5C%5C%5C%5C%28%5Csqrt%5B3%5D%7B2x%20-%206%7D%29%5E3%20%3D%20%28-%5Csqrt%5B3%5D%7B2x%20%2B%206%7D%29%5E3)
Read more on equations here: brainly.com/question/13170908
#SPJ1
Answer: 4
Step-by-step exzplanation: 20/360= X/72
360X= 1440
Divide by 360
X=4